Biomedical, therapeutic and clinical applications of bioactive glasses - Kaur, Gurbinder (Materials scientist) (Woodhead Publishing series in biomaterials., 2019)
"Biomedical, Therapeutic and Clinical Applications of Bioactive Glasses is an essential guide to bioactive glasses, offering an overview of all aspects of the development and utilization of this cutting-edge material. The book covers vital issues, including mesoporosity, encapsulation technologies, scaffold formation and coatings for a number of applications, including drug delivery, encapsulation, scaffolds and coatings. Readers will gain a strong understanding and practical knowledge of the therapeutic aspects of bioceramics, with a focus on glasses from a clinical point-of- view. Researchers, students and scientists involved in bioceramics, bone tissue engineering, regeneration and biomedical engineering will find this to be a comprehensive resource."--Publisher